Melamine modified platinum nanocomposite, preparation method and application thereof

CN118847086BActive Publication Date: 2026-10-16NANCHANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410813850.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-21
Publication Date
2026-10-16
Estimated Expiration
2044-06-21

AI Technical Summary

Technical Problem

[0004]其中铂基催化剂是目前催化甲酸应用最有效的催化剂,然而铂基催化剂由于自身容易出现团聚现象导致催化剂活性降低,因此需要提高铂基催化剂在甲酸溶液内的用量,已达到较高的产氢效率,然而这会导致催化产氢反应的成本较高,亟需提供一种方案改善上述问题

Benefits of technology

[0005] The purpose of this invention is to provide a melamine-modified platinum nanocomposite material, its preparation method and application, which can effectively inhibit the aggregation of platinum nanoparticles and exhibit excellent catalytic activity at room temperature, and can exhibit highly efficient catalytic hydrogen production activity of formic acid even at low platinum content.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118847086B_ABST
    Figure CN118847086B_ABST
Patent Text Reader

Abstract

The application provides a melamine modified platinum nanocomposite and a preparation method and application thereof, and relates to the technical field of hydrogen production catalysts.The preparation method provided by the application comprises the following steps: stirring and reacting melamine, chloroplatinic acid and a reducing agent used for reducing the chloroplatinic acid in a solvent environment at 20-30 DEG C, and then separating to obtain the melamine modified platinum nanocomposite.The production process is simple, green, and low in energy consumption, and the melamine modified platinum nanocomposite can be quickly generated at room temperature without the need of a high-temperature and atmosphere environment, without the need of using an additional surfactant, and the agglomeration of platinum nanoparticles can be effectively inhibited, and the prepared composite material has excellent catalytic activity at room temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of hydrogen production catalyst technology, and in particular to a melamine-modified platinum nanocomposite material, its preparation method, and its application. Background Technology

[0002] With the rapid increase in the world's population and the massive consumption of fossil fuels, global environmental problems are becoming increasingly severe, posing a serious negative impact on the development of human civilization. People are urgently seeking an environmentally friendly, renewable, and sustainable clean energy source. Among various clean energy sources, hydrogen energy, with its high calorific value, ease of storage, biodegradability, and sustainable development, has become an ideal choice. Currently, physical and chemical hydrogen storage methods have been developed; however, due to the difficulty in solving problems such as hydrogen embrittlement in physical hydrogen storage devices, chemical hydrogen storage has become a widely adopted method.

[0003] In recent years, formic acid, borane ammonia, sodium borohydride, hydrazine, and methanol have all been excellent liquid-phase hydrogen storage materials. Among these numerous chemical hydrogen storage materials, formic acid stands out as a very promising liquid-phase hydrogen storage material due to its advantages such as high transport stability, low preparation cost, considerable hydrogen content, and non-flammability. Numerous catalysts for efficient hydrogen production from formic acid have emerged, mainly classified into homogeneous catalysts and heterogeneous catalysts. Since 2008, researchers have developed a large number of stable and highly active noble metal catalysts for the hydrogen production reaction of formic acid.

[0004] Platinum-based catalysts are currently the most effective catalysts for the application of formic acid. However, platinum-based catalysts are prone to agglomeration, which reduces their activity. Therefore, it is necessary to increase the amount of platinum-based catalyst in the formic acid solution to achieve higher hydrogen production efficiency. However, this leads to higher costs for the catalytic hydrogen production reaction. There is an urgent need to provide a solution to improve the above problems. Summary of the Invention

[0005] The purpose of this invention is to provide a melamine-modified platinum nanocomposite material, its preparation method and application, which can effectively inhibit the aggregation of platinum nanoparticles and exhibit excellent catalytic activity at room temperature, and can exhibit highly efficient catalytic hydrogen production activity of formic acid even at low platinum content.

[0006] In a first aspect, the present invention provides a method for preparing melamine-modified platinum nanocomposite materials, wherein melamine, chloroplatinic acid and a reducing agent for reducing chloroplatinic acid are stirred and reacted in a solvent environment at 20-30°C and then separated to obtain melamine-modified platinum nanocomposite materials.

[0007] The preparation method provided by this invention is simple, green and environmentally friendly, and low in energy consumption. It does not require high temperature and atmosphere, and can quickly generate melamine-modified platinum nanocomposite materials at room temperature. It can effectively inhibit the aggregation of platinum nanoparticles without the use of additional surfactants. The prepared composite material has excellent catalytic activity at room temperature.

[0008] Optionally, the method includes the following steps: mixing melamine, chloroplatinic acid and a reducing agent in a solvent environment to obtain a mixture; stirring the mixture at 20-30°C to obtain a dispersion; and separating, washing and drying the dispersion to obtain a melamine-modified platinum nanocomposite material.

[0009] Optionally, when melamine, chloroplatinic acid and reducing agent are mixed, the molar mixing ratio of melamine to chloroplatinic acid is 100:(0.5-1).

[0010] Optionally, a dispersion is obtained by stirring the mixture for 10-30 minutes.

[0011] Optionally, the reducing agent includes at least one of formic acid, sodium borohydride, and ascorbic acid.

[0012] Secondly, the present invention also provides a melamine-modified platinum nanocomposite material, comprising a platinum nanomatrix and melamine modified on the platinum nanomatrix.

[0013] Thirdly, the present invention also provides an application of melamine-modified platinum nanocomposite material in the catalytic production of hydrogen from formic acid.

[0014] Optionally, the process includes the following steps: mixing melamine-modified platinum nanocomposite material with formic acid at 20-30°C and then stirring to react.

[0015] Optionally, when performing catalytic hydrogen production from formic acid, the mass concentration of the melamine-modified platinum nanocomposite material in formic acid is 2-300 mg / L.

[0016] Optionally, the molar concentration of platinum in the melamine-modified platinum nanocomposite material in formic acid is 0.01-0.5 mmol / L. Attached Figure Description

[0017] Figure 1 A flowchart illustrating a method for preparing melamine-modified platinum nanocomposite materials provided by this invention;

[0018] Figure 2 The XRD characterization images are of the melamine-modified platinum nanocomposite material prepared in Example 2 of this invention and the platinum nanoparticles prepared in Comparative Example 1.

[0019] Figure 3The FT-IR spectrum of the melamine-modified platinum nanocomposite material prepared in Example 2 of this invention and melamine is shown below.

[0020] Figure 4 SEM images of the melamine-modified platinum nanocomposite material prepared in Example 2 of this invention and the platinum nanoparticles prepared in Comparative Example 1.

[0021] Figure 5 TEM characterization images of the melamine-modified platinum nanocomposite material prepared in Example 2 of the present invention and the platinum nanoparticles prepared in Comparative Example 1.

[0022] Figure 6 The particle size distribution diagrams are shown for the melamine-modified platinum nanocomposite material prepared in Example 2 of this invention and the platinum nanoparticles prepared in Comparative Example 1.

[0023] Figure 7 The bar chart shows the catalytic hydrogen production activity of the melamine-modified platinum nanocomposites prepared in Examples 1 to 3 of this invention at room temperature.

[0024] Figure 8 The bar chart shows the catalytic activity of the melamine-modified platinum nanocomposite material prepared in Example 2 of this invention for hydrogen production in aqueous formic acid of different concentrations at room temperature.

[0025] Figure 9 The graph shows the catalytic activity changes of the melamine-modified platinum nanocomposite material prepared in Example 2 of this invention during four cycles of catalytic stability testing. Detailed Implementation

[0026] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Unless otherwise defined, the technical or scientific terms used herein should have the ordinary meaning understood by those skilled in the art to which this invention pertains.

[0027] This invention provides a method for preparing melamine-modified platinum nanocomposite materials, comprising stirring and reacting melamine, chloroplatinic acid and a reducing agent for reducing chloroplatinic acid in a solvent environment at 20-30°C, followed by separation, to obtain melamine-modified platinum nanocomposite materials.

[0028] In fact, when chloroplatinic acid and a reducing agent are mixed in a solvent environment, the reducing agent can reduce chloroplatinic acid to generate platinum nanoparticles. Furthermore, after melamine is modified on the surface of the platinum nanoparticles, the aggregation of platinum nanoparticles can be effectively suppressed, and the micro-size of platinum nanoparticles can be controlled.

[0029] In fact, when reducing chloroplatinic acid, there is no need to add surfactants to the reaction system. Instead, melamine has a high dispersing effect, which not only enables the reduced platinum nanoparticles to be uniformly dispersed in the solution system, but also improves the uniformity of melamine modification of platinum nanoparticles, effectively reducing the particle size of platinum nanoparticles.

[0030] Specifically, see Figure 1 The method for preparing melamine-modified platinum nanocomposite materials provided by the present invention includes the following steps:

[0031] S1. Melamine, chloroplatinic acid and a reducing agent are mixed in a solvent environment to prepare a mixture;

[0032] S2. The mixture is stirred and reacted at 20-30℃ to obtain a dispersion.

[0033] S3. The dispersion was separated, washed, and dried to obtain melamine-modified platinum nanocomposite material.

[0034] In some embodiments, the reducing agent used in step S1 includes at least one of formic acid, sodium borohydride, and ascorbic acid. In practice, any commonly used reagent capable of reducing chloroplatinic acid can be used as the reducing agent. However, for economic reasons, formic acid is preferred. Specifically, when formic acid is used as the reducing agent, it can be pure formic acid or a mixture of formic acid and water in any proportion.

[0035] In some embodiments, after mixing melamine, chloroplatinic acid, and the reducing agent in step S1, the molar mixing ratio of melamine to chloroplatinic acid is 100:(0.5-1). In fact, by controlling the content of melamine in the mixture, the reduction rate of chloroplatinic acid by the reducing agent can be affected, thereby controlling the amount and morphology of melamine modification on the surface of platinum nanoparticles, and consequently controlling the specific surface area, catalytic active sites, and catalytic efficiency of the composite material.

[0036] In some embodiments, when the reducing agent is an aqueous formic acid solution, melamine and chloroplatinic acid can be directly added to the aqueous formic acid solution for mixing during step S1. Specifically, melamine can be mixed in solid form or in solution form. In practice, when mixing to obtain the mixture, commonly used mixing methods in the art can be employed, such as mechanical stirring or ultrasonic mixing, to ensure that the mixture is uniformly dispersed.

[0037] In some embodiments, during step S2, the mixture is stirred at 20-30°C for 10-30 minutes to obtain a dispersion. In fact, controlling the stirring time helps to regulate the reduction amount of chloroplatinic acid and the amount and degree of melamine modification of platinum nanoparticles.

[0038] In some embodiments, when performing step S2, the mixture can react in any gas atmosphere such as air or nitrogen, as long as the gas atmosphere does not react with the mixture system.

[0039] In some embodiments, when performing separation in step S3, commonly used separation methods in the art can be employed, such as filtering or centrifuging the dispersion, to ensure that the solids within the dispersion are separated individually. In reality, the resulting solids are melamine-modified platinum nanocomposites, which also contain unmodified melamine and other impurities.

[0040] In some embodiments, when performing step S3 for washing, deionized water can be used to rinse the separated solids to remove solids adhering to the composite material, thereby improving the purity of the obtained melamine-modified platinum nanocomposite material.

[0041] In some embodiments, during the drying process in step S3, the washed solids are transferred to a drying oven and dried to a constant weight to obtain the final product—melamine-modified platinum nanocomposite material.

[0042] This invention also provides a melamine-modified platinum nanocomposite material prepared by any of the above-described preparation methods, comprising a platinum nanomatrix and melamine modified on the surface of the platinum nanomatrix. In fact, by modifying the surface of the platinum nanomatrix with melamine, the specific surface area of ​​the composite material can be increased, and the catalytic active sites can be enhanced.

[0043] Specifically, this invention also provides the application of the above-mentioned melamine-modified platinum nanocomposite material in the catalytic production of hydrogen from formic acid. By stirring and mixing the composite material with formic acid at room temperature and pressure, the formic acid decomposes to produce hydrogen and carbon dioxide. In practice, the formic acid used in catalytic hydrogen production can be a pure methanol solution or a mixture of formic acid and water in any proportion. Specifically, the higher the formic acid concentration, the higher the catalytic hydrogen production efficiency.

[0044] In some embodiments, to achieve better reaction efficiency and balance reaction costs during the catalytic production of hydrogen from formic acid, the optimal mass concentration of the melamine-modified platinum nanocomposite material in formic acid is 2-300 mg / L. However, this optimal range does not impose a limitation on the amount of composite material used. It is important to understand that the melamine-modified platinum nanocomposite material can catalyze the production of hydrogen from formic acid whenever it enters formic acid.

[0045] In some embodiments, during the catalytic hydrogen production from formic acid, the melamine-modified platinum nanoparticles are mixed with formic acid, and the molar concentration of platinum in the formic acid is 0.01-0.5 mmol / L. Similarly, this molar concentration limitation does not impose a limitation on the amount of composite material used. It should be noted that the higher the concentration of platinum in the formic acid, the higher the catalytic efficiency.

[0046] Example 1

[0047] Example 1 of this invention provides a method for preparing melamine-modified platinum nanocomposite materials, comprising the following steps:

[0048] S1. Add 100 mg of melamine to a 500 mL sealed Pyrex reaction flask, and add 4 mL of 1.93 mmol / L chloroplatinic acid solution and 96 mL of formic acid. After tightening the cap, mix the mixture by ultrasonication to obtain a mixture.

[0049] S2. Use nitrogen blowing to purge the contents of the light-exposed bottle for 20 minutes, and place the Pyrex reaction bottle on a magnetic stirrer at 25°C. Stir the mixture at a constant speed for 10-30 minutes to obtain a dispersion.

[0050] S3. The Pyrex reaction flask was centrifuged at 15,000 rpm to separate the precipitate. The precipitate was washed with pure water and then dried in a drying oven at 60°C to obtain melamine-modified platinum nanocomposite material (Pt / MA).

[0051] Example 2

[0052] Example 2 of the present invention provides a method for preparing platinum nanocomposite material, which differs from Example 1 in that the amount of melamine added in step S1 is 150 mg.

[0053] Example 3

[0054] Example 3 of the present invention provides a method for preparing platinum nanocomposite material, which differs from Example 1 in that the amount of melamine added in step S1 is 200 mg.

[0055] Comparative Example 1

[0056] Comparative Example 1 of this invention provides a method for preparing platinum nanoparticles, comprising the following steps:

[0057] D1. Add 4 mL of 1.93 mmol / L chloroplatinic acid solution and 96 mL of formic acid to a 500 mL sealed Pyrex reaction flask, tighten the cap, and then mix by ultrasonication to obtain a mixture.

[0058] D2. Use nitrogen blowing to purge the Pyrex reaction flask for 20 minutes, and place the flask on a magnetic stirrer at 25°C. Stir the mixture at a constant speed for 10-30 minutes to obtain a dispersion.

[0059] D3. The Pyrex reaction flask was centrifuged at 15,000 rpm to separate the precipitate. The precipitate was washed with pure water and then dried in a drying oven at 60°C to obtain platinum nanomaterials (Pt).

[0060] Morphological representation

[0061] The melamine-modified platinum nanocomposite material (Pt / MA) prepared in Example 2 and the platinum nanoparticles (Pt) prepared in Comparative Example 1 were characterized by X-ray diffraction. The characterization results are as follows: Figure 2 As shown;

[0062] The melamine-modified platinum nanocomposite material (Pt / MA) and melamine (MA) prepared in Example 2 were characterized using an infrared spectrometer (Gary 630FTIR, Agilent). Their spectra are shown below. Figure 3 As shown;

[0063] The platinum nanoparticles (Pt) prepared in Comparative Example 1 and the melamine-modified platinum nanocomposite material (Pt / MA) prepared in Example 2 were characterized by scanning electron microscopy (SEM), as shown below. Figure 4 (a) and Figure 4 As shown in (b);

[0064] The platinum nanoparticles (Pt) prepared in Comparative Example 1 and the melamine-modified platinum nanocomposite material (Pt / MA) prepared in Example 2 were characterized by transmission electron microscopy (TEM), as shown below. Figure 5 (a) and Figure 5 As shown in (b):

[0065] The particle size distribution of platinum nanoparticles (Pt) prepared in Comparative Example 1 and melamine-modified platinum nanocomposite material (Pt / MA) prepared in Example 2 was detected using transmission electron microscopy (TEM, JEOL, JEM-2100). The detection results are shown below. Figure 6 (a) and Figure 6 (b)

[0066] from Figure 2 As can be seen, compared with the platinum nanoparticles (Pt) prepared in Comparative Example 1, the peak positions and corresponding diffraction peak intensities in the XRD pattern of the melamine-modified platinum nanocomposite material (Pt / MA) prepared in Example 1 did not change significantly. This indicates that even after modification with melamine, the composite material (Pt / MA) still maintains the same crystal structure as the platinum nanoparticles (Pt).

[0067] from Figure 3 It can be seen that melamine (MA) is located between 3500 and 3300 cm⁻¹. -1 The peaks are sharp absorption bands, typical stretching vibration peaks of free NH bonds, and correspond to the CN and C=N functional groups in melamine, respectively. In Pt / MA, the peaks are located between 3500 and 3200 cm⁻¹. -1 The peak of Pt / MA is a broad absorption band, and compared with melamine at the same wavenumber, the peak position of Pt / MA shifts to a lower wavenumber. This indicates that Pt / MA contains multi-molecular associated NH bonds. Therefore, it can be inferred that melamine in Pt / MA forms intermolecular hydrogen bonds through NH bonds, thereby modifying the surface of platinum nanoparticles.

[0068] from Figure 4 (a) It can be seen that the platinum nanoparticles (Pt) prepared in Comparative Example 1 without surface modification using melamine are prone to agglomeration, forming large particles with a diameter in the micrometer range (6.23 μm). Figure 4 (b) It can be seen that the particle size of Pt / MA after melamine modification is greatly reduced and no agglomeration occurs. This shows that melamine modification can not only reduce the particle size of the composite material, but also inhibit agglomeration.

[0069] from Figure 5 (a) and Figure 5 (b) It can be seen that both the platinum nanoparticles (Pt) prepared in Comparative Example 1 and the composite material (Pt / MA) prepared in Example 1 expose the (111) crystal plane of platinum with a spacing of 0.226 nm; at the same time, Figure 5 (b) A layer of white melamine can be observed suspended on the surface of the particles, but no lattice fringes of white melamine are observed under high magnification transmission electron microscopy, which indicates that the dispersion of platinum nanoparticles in Pt / MA is improved.

[0070] from Figure 6 (a) It can be seen that the average particle size of the platinum nanoparticles (Pt) prepared in Comparative Example 1 is 2.8 ± 0.6 nm. Figure 6(b) It can be seen that the average particle size of the composite material (Pt / MA) prepared in Example 1 is 1.8 ± 0.6 nm, and the particle size concentration of Pt / MA is higher than that of Pt. This indicates that melamine surface modification can improve the particle size and particle size uniformity of platinum nanoparticles.

[0071] Catalytic performance testing

[0072] The melamine-modified platinum nanocomposites prepared in Examples 1 to 3 were mixed with 100 mL of a 2 mol / L formic acid aqueous solution, and the mixtures were stirred at 25°C for 1 h. The hydrogen evolution rate was then measured. Figure 7 As shown.

[0073] The melamine-modified platinum nanocomposite material (Pt / MA) prepared in Example 2 was used to catalyze hydrogen evolution in 100 mL formic acid solutions with concentrations of 0.2, 0.5, 0.7, 1.0, 1.5, and 2.0 mol / L. The hydrogen evolution rates of Pt / MA catalyzing formic acid solutions of different concentrations are as follows: Figure 8 As shown.

[0074] The melamine-modified platinum nanocomposite material (Pt / MA) prepared in Example 2 was used to catalytically decompose a 2 mol / L formic acid solution at room temperature. The catalyst and formic acid solution were not replaced during the catalytic process. Catalysis was continued for four cycles, each lasting 5 hours. The hydrogen evolution rate of Pt / MA in each cycle was measured. Figure 9 As shown.

[0075] from Figure 7 As can be seen, gradually increasing the relative amount of melamine added within a certain range during the preparation of melamine-modified platinum nanocomposites can improve the catalytic activity of the obtained composite material. For example, the Pt / MA prepared in Example 2 showed relatively good catalytic activity, reaching 56.4 mmol / h. -1 g Pt -1 However, adding too much melamine can actually reduce catalytic activity.

[0076] from Figure 8 As can be seen, in the catalytic hydrogen production from formic acid, the formic acid concentration is positively correlated with the hydrogen production rate; a higher formic acid concentration promotes the hydrogen evolution activity of Pt / MA. Figure 9 As can be seen, the Pt / MA provided by this invention exhibits high stability during cyclic hydrogen evolution tests, and its catalytic activity does not decrease significantly within 15 hours.

[0077] While embodiments of the present invention have been described in detail above, it will be apparent to those skilled in the art that various modifications and variations can be made to these embodiments. However, it should be understood that such modifications and variations fall within the scope and spirit of the invention as set forth in the claims. Furthermore, the invention described herein may have other embodiments and can be implemented or carried out in various ways.

Claims

1. A method for preparing melamine-modified platinum nanocomposite materials, characterized in that, Includes the following steps: A mixture is prepared by mixing melamine, chloroplatinic acid, and a reducing agent for reducing chloroplatinic acid in a solvent environment; the molar ratio of melamine to chloroplatinic acid is 100:(0.5-1); the reducing agent is formic acid. The mixture was stirred at 20-30°C for 10-30 minutes to obtain a dispersion. The dispersion was separated, washed, and dried to obtain a melamine-modified platinum nanocomposite material.

2. A melamine-modified platinum nanocomposite material prepared by the method described in claim 1, characterized in that, It includes a platinum nanomatrix and melamine modified on the platinum nanomatrix.

3. The application of a melamine-modified platinum nanocomposite material prepared by the preparation method described in claim 1, or the melamine-modified platinum nanocomposite material described in claim 2, in the catalytic production of hydrogen from formic acid.

4. The application according to claim 3, characterized in that, The process includes the following steps: mixing melamine-modified platinum nanocomposite material with formic acid at 20-30℃ and then stirring to react.

5. The application according to claim 3, characterized in that, When performing catalytic hydrogen production from formic acid, the mass concentration of the melamine-modified platinum nanocomposite material in formic acid is 2-300 mg / L; and / or, the molar concentration of platinum in the melamine-modified platinum nanocomposite material in formic acid is 0.01-0.5 mmol / L.